Challenges and future prospects of online practical education in physical education faculties during the COVID-19 pandemic - O.M. Abdel Fattah; A.A. Zureigat; S.H. Qasim; M.A. Alzughailat; A.S. Khasawneh (Образование и наука)
Introduction. Coronavirus (COVID-19) is considered a worldwide pandemic, and as such a threat, it caused millions of cases and above million deaths.Aim. The present research aims to explore the challenges among the lecturers and students during the online practical education in the faculties of physical education (PE) during the COVID-19 world pandemic, and to seek the best solutions and applications that can be used under similar circumstances from the perspective of lecturers and students.Methodology and research methods. The authors used the descriptive approach on a sample of lecturers (n = 63) and students (n = 1391). To reduce face-to-face interaction, the researchers designed the study tool using a web tool, where the study included two questionnaires. The first dealt with the lecturers’ challenges during the online practical education and the best solutions and practices from their perception. In addition, the second dealt with the students’ challenges during the online practical education and the best solutions and techniques from the students’ points of view. We used frequencies, percentages, Cronbach’s alpha coefficient, mean, standard deviations, three-way ANOVA, and Scheffe test to address the study sample responses.Results. The findings show that the educational environment is one of the main challenges facing the lecturers during the online practical education while considering the aspects of students’ social and economic factors is one of the essential solutions. In addition, there are statistically significant differences in the level of challenges according to the gender variable. From the students’ points of view, the content and the educational environment are among the most significant challenges they face during online practical education.Scientific novelty. The study attempted to uncover the challenges facing students in physical education faculties in practical subjects. As far as the researchers know, it is considered one of the few studies that addressed the impact of the transition to distance education due to the Coronavirus pandemic. Therefore, this study constitutes a turning point that can be used in future studies.Practical significance. The practical significance of this study lies in the use of its results in strategic planning for distance education in similar situations, thus contributing to achieving better learning outcomes by addressing weaknesses and encouraging positive aspects.